Sex and gender disparities in lupus nephropathy and kidney transplantation - Marcora Mandreoli (AboutScience Srl, 2023)
Systemic lupus erythematosus (SLE) has a clear prevalence in females. Although there are conflicting data, among males affected by SLE a higher proportion develops lupus nephritis, with a more severe histological and clinical pattern than in females. More frequently males also present an antiphospholipid syndrome. Males are less likely to achieve clinical remission of lupus nephritis. A sex and gender disparity is also present in all the phases preceding the kidney transplant from the referral for eligibility to the registration on the active waiting list. There is a perception among healthcare staff that women have a greater degree of fragility and are therefore less eligible for kidney transplantation. Women also encounter obstacles in completing the tests necessary for inclusion in the waiting list and in many Health Care contexts they are less likely to have a transplant. In the field of living transplantation, women represent over half of all donors, while males are predominantly recipients. Long-term patient and graft survival appears superior in women than in men.